2022
DOI: 10.1101/2022.07.31.502239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis for assembly and lipid-mediated gating of LRRC8A:C volume-regulated anion channels

Abstract: Leucine-rich repeat-containing protein 8 (LRRC8) family members form volume regulated anion channels activated by hypoosmotic cell swelling. LRRC8 channels are ubiquitously expressed in vertebrate cells as heteromeric assemblies of LRRC8A (Swell1) and LRRC8B-E subunits. Channels of different subunit composition have distinct properties that explain the functional diversity of LRRC8 currents implicated in a broad range of physiology. However, the basis for heteromeric LRRC8 channel assembly and function is unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
(125 reference statements)
1
3
0
Order By: Relevance
“…Importantly, we observed two layers of density resembling lipid bilayer blocking the pore of the 8C-8A(IL1 25 ) heptameric channel ( Figure 7 and Figure 7—figure supplement 1 ). In agreement with our observations, in a recent pre-print reporting the hexameric structure of LRRC8A-LRRC8C ( Kern et al, 2022 ), ordered lipid molecules are observed on the extracellular side of the pore opening aligning well with the densities we observed. Intrapore lipids have recently been proposed to be critical structural and regulatory elements of pannexins ( Kuzuya et al, 2022 ) and closely related innexin ( Burendei et al, 2020 ) and CALHM ( Drożdżyk et al, 2020 ; Syrjanen et al, 2020 ) channels, as well as bacterial mechanosensitive channels ( Rasmussen et al, 2019 ; Reddy et al, 2019 ; Zhang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Importantly, we observed two layers of density resembling lipid bilayer blocking the pore of the 8C-8A(IL1 25 ) heptameric channel ( Figure 7 and Figure 7—figure supplement 1 ). In agreement with our observations, in a recent pre-print reporting the hexameric structure of LRRC8A-LRRC8C ( Kern et al, 2022 ), ordered lipid molecules are observed on the extracellular side of the pore opening aligning well with the densities we observed. Intrapore lipids have recently been proposed to be critical structural and regulatory elements of pannexins ( Kuzuya et al, 2022 ) and closely related innexin ( Burendei et al, 2020 ) and CALHM ( Drożdżyk et al, 2020 ; Syrjanen et al, 2020 ) channels, as well as bacterial mechanosensitive channels ( Rasmussen et al, 2019 ; Reddy et al, 2019 ; Zhang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Two recent studies have defined high-resolution cryo-EM structures of LRRC8A/LRRC8C heteromeric channels ( Kern et al, 2022 ; Rutz et al, 2023 ). Both studies demonstrated that the heteromeric channels could adopt a hexameric conformation with a limiting pore radius of 2–3 Å, similar to that of LRRC8A hexamers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To operate efficiently, VRAC necessitates the presence of LRRC8A and at least one subunit among the LRRC8B-E isoforms [17,18]. Recently, in cryoEM studies of heteromeric LRRC8A/ LRRC8C complexes, different stoichiometries have been reported: Rutz et al found 4 LRRC8A subunits and 2 LRRC8C subunits in heteromers [21], while Kern et al reported a 5 LRRC8A/1 LRRC8C architecture [22]. In general, most cells express more than two different LRRC8 genes and LRRC8A-E assemble in various configurations, leading to the formation of VRACs with differing functional characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In TRAAK, a eukaryotic mechanosensitive channel, occlusion of the pore by a lipid acyl chain has been proposed as a gating mechanism 13,22 . In the volume-regulated channel SWELL1 lipids block the pore in the closed state 23 . In the bacterial mechanosensitive channel MscS, the occupation of lipid pockets may determine channel conformation 24,25 , and in FLYC1, a Venus flytrap homolog of MscS, conformational changes may allow lipids to access the pore and occlude ion conduction 26 .…”
Section: Substitution Of Potential Lipid-interacting Lysine Residues ...mentioning
confidence: 99%